Kesiapan Pelaksanaan Rekam Medis Elektronik (RME) dengan Pendekatan 5 M (Man, Money, Material, Machine, Methode): Studi Kasus RSUM Ponorogo - Ria Fajar Nurhastuti (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Electronic Medical Records (EMR) are medical records compiled and stored through an electronic system used to support the provision of healthcare services. The implementation of EMR facilitates faster, more practical, and integrated patient data recording. Electronic Medical Records (EMR) are designed to improve the efficiency, accessibility, and accuracy of patient information within healthcare institutions. This study used a qualitative descriptive approach with a case study design through interviews to assess the readiness of EMR implementation in terms of the 5M management aspects (Man, Money, Material, Machine, Method) at Muhammadiyah General Hospital, Ponorogo Regency. The study sample consisted of 27 healthcare workers selected using a purposive sampling technique. The case study design allowed researchers to capture in-depth insights from healthcare workers directly involved in EMR implementation. The results showed that from the Man element, most healthcare workers were ready to use EMR, as indicated by their comfort and skills in operating the application. In the Money element, there is a system maintenance budget and support for EMR development in the inpatient unit and the Emergency Room. The Material element indicates the availability of adequate software, while the Machine element includes computer devices, internet connections, and a stable server to support users. These technological resources ensure a user-friendly and reliable system. The final element, Method, is demonstrated by the existence of clear SOPs and workflows, enabling healthcare workers to understand and effectively follow the EMR implementation process. Overall, the findings indicate that the hospital is institutionally prepared for EMR adoption.